1995
DOI: 10.1034/j.1399-3054.1995.940109.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an assay for Mg-dechelatase of oilseed rape cotyledons, using chlorophyllin as the substrate

Abstract: Development of an assay for Mg-dechelatase of oilseed rape cotvledons. using chlorophvilin as the substrate. -Phvsiol. Plant. 94: 57-63.Chlorophyllin (Chlin). the Mg-chlorin obtained from chlorophyll (Chi) was employed as substrate of Mg-dechelatase. The release of Mg-* was associated with a shift of absorption from 644 to 687 nm. Changes of absorption at 687 nm were taken as a measure of Mg-dechelatase activity present in preparations of oilseed rape thylakoids. Absorption changes were correlated linearly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 7 publications
2
40
1
Order By: Relevance
“…Different types of activities Plant Mol Biol (2013) 82:505-517 509 have been described in the past, one attributed to a heatstable low-molecular weight compound, termed metalchelating substance (MCS) (Shioi et al 1996a;Suzuki and Shioi 2002), the other attributed to heat-labile proteins, termed Mg-releasing proteins (MRP) (Suzuki and Shioi 2002;Vicentini et al 1995b). However, MRP activity could so far only been shown when using chlorophyllin, i.e.…”
Section: Mg-dechelation and Dephytylationmentioning
confidence: 99%
“…Different types of activities Plant Mol Biol (2013) 82:505-517 509 have been described in the past, one attributed to a heatstable low-molecular weight compound, termed metalchelating substance (MCS) (Shioi et al 1996a;Suzuki and Shioi 2002), the other attributed to heat-labile proteins, termed Mg-releasing proteins (MRP) (Suzuki and Shioi 2002;Vicentini et al 1995b). However, MRP activity could so far only been shown when using chlorophyllin, i.e.…”
Section: Mg-dechelation and Dephytylationmentioning
confidence: 99%
“…Chlorophyllins were prepared from chlorophylls by Molisch conversion as described by Vicentini et al (1995). One hundred µl of 30% KOH in methanol was added to 12 ml of chlorophyll solution in petroleum ether.…”
Section: Preparation Of Chlorophylls and Chlorophyllins For Enzyme Asmentioning
confidence: 99%
“…The dechelation of magnesium from chlorophyllin (or chlorophyllide) to form pheophorbide was determined by monitoring the change in absorbance with time at 686 nm according to Vicentini et al (1995) and Janave (1997). The assay mixture was comprised of 830 µl 50 mM Tris-Tricine (pH 8.0), 50 µl chlorophyllin (A 686 nm = 0.18), 100 µl of 1% Triton X-100, and 20 µl of enzyme extract.…”
Section: Preparation Of Chlorophylls and Chlorophyllins For Enzyme Asmentioning
confidence: 99%
See 1 more Smart Citation
“…chelating substances (MCS) or by Mg-releasing proteins (MRP), which differs by their substrate specificity. 19,20 We found that A9:u-ATP9 and ap3:u-ATP9 plants presented an increase of 25 and 40% of the Mg-dechelatase activity respectively compared with wild-type plants (Fig. 3).…”
mentioning
confidence: 88%